Employees' emotions in change: advancing the sensemaking approach. Issue 6 (3rd October 2016) - Helpap, Sevda; Bekmeier-Feuerhahn, Sigrid
Abstract : Purpose: Organizational changes are emotionally charged processes, and scholarly research has increasingly emphasized the impact of employee emotions on successful change management. This impact has rarely been considered in light of approaches focussing on employee sensemaking. To address this critical gap, the purpose of this paper is to combine the model of enacted sensemaking with insights from the Affect Infusion Model. Design/methodology/approach: To test the model, the authors surveyed 261 employees with a vignette study and performed structural equation modeling on the results. Findings: The findings reveal that emotions significantly affect employees' level of psychological resources, particularly change commitment, efficacy, and expectations. Furthermore, change commitment and efficacy are significant predictors of resistance intention, which confirms (to an extent) the validity of enacted sensemaking, and these factors mediate the relationship between employees' emotions and their resistance intentions. Research limitations/implications: This study focussed on the early stages of a change initiative. Therefore, the authors only considered employee assessment at one point in time. Practical implications: This model has managerial utility for explaining how employees' resistance intention regarding change is influenced by employees' emotions and their psychological resources. Originality/value: The results broaden the horizons because they suggest a model of "emotionally primed" enacted sensemaking for employees during organizational change by offering a new theoretical framework (enacted sensemaking and substantive processing) and a new methodological approach (quantitative vignette study).